Moving the mountain : a new vision of Islam in America - Abdul Rauf, Feisal, 1948- (New York : Free Press, 2012)
In this book the Muslim leader best known for his contributions to the establishment of an interfaith community center near Manhattan's Ground Zero offers insight into his progressive beliefs and advocacy of tolerance and equal rights. Muslims in America who reject extremist or fundamentalist expressions of Islam at home and abroad feel the urgent need for a voice that can represent them in the current debate about Islam, America, and the West. Imam Feisal Abdul Rauf, the so-called Ground Zero Imam, has become that voice. This is his vision for a new, American Islam.
What we believe -- Shariah in America -- Islam and other religions -- The modern American Muslim woman -- Our fight against extremism -- Islam, the state, and politics -- Islam the American way.
Includes index.
Includes bibliographical references (p. 201-205) and index.
Keywords: Islam -- United States; Muslims -- United States